Nonadditive and Asymmetric Allelic Expression of Growth Hormone in Hybrid Tilapia - Zhong, Huan; Zhang, Xiaojin; Xu, Qian; Yan, Jinpeng; Han, Zhuojun; Zheng, Huifang; Xiao, Jun; Tang, Zhanyang; Wang, Fenghua; Luo, Yongju; Zhou, Yi (Frontiers in Genetics, 2019)
Hybridization is a common breeding technique that can improve germplasm through heterosis in aquaculture. However, the regulation of key gene expression, including the details of transcriptional level changes at the beginning of hybridization events, remains largely undefined, especially in teleosts. In this study, by interspecies crossing between two pure lines of Nile tilapia and blue tilapia, we obtained a hybrid tilapia population as a model to elucidate heterosis, and we traced the molecular outcomes of growth hormone (GH) expression and allele-specific expression (ASE) in hybrids. The hybrids display growth vigor compared to their parents in the 120-day growth trial. GH mRNA expression was uniquely expressed in the pituitary. The overall expression of GH in the hybrid was significantly higher than in its parents. In addition, higher GH expression was found in the hybrid than the mid-parent value, in both males and females, showing a non-additive pattern. We identified four SNP sites between Nile tilapia and blue tilapia. Subsequently, by pyrosequencing, we found asymmetric allelic expression in hybrids with higher maternal allelic transcript ratios in both males and females. Fasting significantly increased GH expression in hybrids, but asymmetric allelic expression was not affected by feeding or fasting conditions. Finally, we identified cis and trans effects via overall expression and ASE values in the hybrid, which showed that the cis and trans effects promoted the expression of maternal subgenome in the hybrid, contributing to the expression superiority of GH in hybrid tilapia. Taken together, the results of our study first illustrated the concept of GH expression superiority and its formation mechanism in hybrid fish with growth vigor.